EFEKTIVITAS KEBIJAKAN PROGRAM KARTU JAKARTA MAHASISWA UNGGUL SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN MAHASISWA PROVINSI DKIJAKARTA : Studi Kasus Mahasiswa UPN "Veteran" Jakarta - Axcel Deyong Aponno (2022)
The policies of the central and regional governments in various fields have changed from time to time, often with changes in leadership. Education is one of the fields that has undergone major changes from the highest norms with a long history as an effort to realize the national ideals contained in it. This history brought about policy changes in the field of education which were expanded with the authority of local governments to help improve the quality of education in their regions. DKI Jakarta Province is one of the provinces in Indonesia that makes a policy of providing educational funding assistance for students with the Jakarta Student Excellence Card (KJMU) program. The KJMU program is given by the DKI Jakarta Provincial Government to students who live in DKI Jakarta to be able to continue their education at various universities in Indonesia. UPN "Veteran" Jakarta as a state university is one of the places where students take higher education using the KJMU program. The research method used is empirical juridical, with a statute approach and a case approach supported by primary and secondary data. The purpose of this study was to determine the effectiveness of the KJMU program policy as an effort to improve the quality of education in the DKI Jakarta Province. The results of this study explain that the KJMU program policy owned by DKI Jakarta Province is an effective policy in helping students to continue their education to a higher level, so that the ideals of the nation and state in educating the nation's life can be realized. Therefore, it is necessary to evaluate and increase the level of education from the program to master's and doctoral degrees.